‘Iddah Wanita Hamil Karena Zina Menurut Hukum Islam dan Hukum Positif - Rizqa Febry Ayu (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
'Iddah is a common problem, but when faced with special conditions such as women who commit adultery, it becomes a complicated problem and differences of opinion arise among scholars. The scholars differ in their opinion in determining whether or not there is an 'iddah for pregnant women due to adultery. The author discusses three problems. First, how are the provisions of Islamic law to determine the 'iddah for adulterers, Second, how according to the provisions of positive law to determine the 'iddah for adulterers, Third, the arguments and methods used in fiqh to determine the 'iddah for adulterers. This research was conducted with a qualitative approach, with the type of literature research (library research). The results of the study found that the provisions of Islamic law on 'iddah for pregnant women due to adultery are that there are two opinions according to the scholars that the Shafi'i and Hanafi schools do not require 'iddah, and are allowed to marry the woman, because interfering in the form of adultery does not cause nasab relations. then it is not forbidden to marry this woman. The Maliki and Hanbali schools oblige the woman to perform her iddah, if she is pregnant then her iddah is until she gives birth, and if there is no visible pregnancy, her iddah is three times holy. Second, the positive legal provisions on 'iddah for pregnant women because of adultery also do not explain specifically about 'iddah for pregnant women due to adultery. Both in Law Number 1 of 1974 and in Government Regulation Number 9 of 1975. Third, the arguments and methods used in fiqh to determine the 'iddah for pregnant women due to adultery are according to the Shafi'i school using the provisions of QS.An -Nisa verse 24 and the hadith of the Prophet from Aisha, ra. According to the Hanafi school, it is based on the hadith of the Prophet. According to the Maliki school of thought, it comes from the words of Ibn Mas'ud, and according to the Hanbali school it comes from the QS. An-Nur verse 3.